Innovation in the High-Tech Economy - Chuan, Pang.; Chuan, Pang.; Khachidze, Vasil.; Khachidze, Vasil.; Lai, Ivan K.W.; Lai, Ivan K.W.; Liu, Yide.; Liu, Yide.; Siddiqui, Sohail.; Siddiqui, Sohail.; Wang, Tim.; Wang, Tim. (Contributions to Economics, 2013)
This book constitutes the proceedings of the First International Conference on Management Science and Engineering: Innovation and High-tech Services, ICMSE 2013, held in Macau, in June 2013. The papers are contributed by innovative researchers, engineers and practitioners in the field of management science, information system, finance, economics and accounting and offer a platform for exchanging the latest research findings in the field of management science and management innovation, for looking forward to the future trends in the management science and management innovation field in the 21st century, and to promote management modernization and high-tech innovation services.